Weichselian phases and ice dynamics of the Scandinavian Ice Sheet in Northeast Germany - Hardt, Jacob (2017)
The glacial formation of the young morainic landscape of northeast Germany has been investigated for more than 100 years. Different Weichselian advances of the Scandinavian Ice Sheet into northeast Germany were differentiated on basis of morphological and sedimentological findings. The chronology of the different phases was mostly based on long-distance correlations of radiocarbon ages or estimates. In recent years, a number of studies have shown that these traditional models require revision. Modern dating methods allow for direct dating of glaciofluvial or glacigenic deposits and high resolution digital elevation models reveal morphological details of the glacial landscape, which give new insights in the dynamics of the inland ice. In this study, Optically Stimulated Luminescence (OSL) dating was applied to determine depositional ages of glaciofluvial sediments belonging to the Weichselian Brandenburg and Frankfurt phases at study sites in Brandenburg. The ice advance during the Brandenburg phase was dated to 34.1 ± 4.6 ka. The formation of the Brandenburg ice marginal position was dated to 30 ± 4 ka. For the first time the Frankfurt phase, the succeeding meltdown phase, was dated to 26.3 ± 3.7 ka. A landscape stabilization phase, as indicated by recalibrated exposure ages of glacigenic boulders, set in at around 24 ± 2 ka in middle Brandenburg. A phase of aeolian activity, possibly triggered by medieval human activity, was dated to ~1 ka. Previously published cosmogenic exposure ages from erratic boulders were recalculated with an up-to-date 10Be production rate, which significantly increased the ages. After recalculation, the cosmogenic exposure and OSL ages provide a consistent geochronological data base, which confirms a two-fold last glacial maximum in Brandenburg. The largest Weichselian ice-extent occurred during the Brandenburg phase in late marine isotope stage 3. This advance correlates with the Klintholm advance in Denmark and possibly an advance in middle Poland. At the time of the global last ...